Religion and the Prevention of Hate Speech: Increasing Inclusivity through the Concept of the Malaysian Family - Nordin, Munif Zarirruddin Fikri (Advances in Social Sciences Research Journal, 2022)
Religion plays an important role in the prevention of hate speech through the spiritual aspect as well as the morality aspect, particularly in differentiating between good and bad, and right and wrong. In Malaysia, the latest concept, that of ‘the Malaysian Family’ (Keluarga Malaysia), which was introduced in October 2021, embraces three characteristics, namely inclusivity, common ground, and contentment. The enrichment of values under these characteristics mainly focuses on strengthening the big family of Malaysia, including the prevention of hate speech. However, what are the religious values in the concept of the Malaysian Family and how to increase inclusivity through the concept to prevent hate speech need to be studied. This study aims to (1) identify the religious values in the concept of the Malaysian Family, that pertain to the prevention of hate speech, and (2) explain the strategy for increasing inclusivity through the concept to prevent hate speech. The data of the study comprise the religious values, related to courtesy and morality, taken from the Quran, as well as the seven enriching values that fall under the characteristic of inclusivity in the concept. The findings show that there are a number of religious values related to courtesy and morality in the concept, which pertain to the prevention of hate speech. The findings also show that the seven enriching values under the characteristic of inclusivity in the concept, need effective strategies for preventing hate speech, such as enhancing the role of religious leaders and the media.